Excitation‐Dependent Photoluminescence from Single‐Carbon Dots. Issue 48 (9th November 2017) - van Dam, Bart; Nie, Hui; Ju, Bo; Marino, Emanuele; Paulusse, Jos M. J.; Schall, Peter; Li, Minjie; Dohnalová, Katerina
Abstract: Carbon dots (CDs) are carbon‐based fluorescent nanoparticles that can exhibit excitation‐dependent photoluminescence (PL) "tunable" throughout the entire visible range, interesting for optoelectronic and imaging applications. The mechanism underlying this tunable emission remains largely debated, most prominently being ascribed to dot‐to‐dot variations that ultimately lead to excitation‐dependent ensemble properties. Here, single‐dot spectroscopy is used to elucidate the origin of the excitation‐dependent PL of CDs. It is demonstrated that already single CDs exhibit excitation‐dependent PL spectra, similar to those of the CD ensemble. The single dots, produced by a facile one‐step synthesis from chloroform and diethylamine, exhibit emission spectra with several characteristic peaks differing in emission peak position and spectral width and shape, indicating the presence of distinct emission sites on the CDs. Based on previous work, these emission sites are related to the sp 2 subregions in the carbon core, as well as the functional groups on the surface. These results confirm that it is possible to integrate and engineer different types of electronic transitions at the nanoscale on a single CD, making these CDs even more versatile than organic dyes or inorganic quantum dots and opening up new routes toward light‐emission engineering. Abstract : Using single‐dot spectroscopy individual carbon dots are shown to already exhibit excitation‐dependent photoluminescence, very similar to the ensemble of carbon dots. Characteristic excitation‐dependent emission spectra are identified, indicating the presence of multiple active emission sites within a single carbon dot. This shows that it is possible to engineer different types of electron transitions at the nanoscale through facile chemical synthesis.